PELATIHAN MODEL PEMBELAJARAN BERBASIS LITERASI DAN NUMERASI BAGI GURU UPTD SD NEGERI 4 PAKUAN AJI - Aini, Nurul; Setyawati, Astri; Festiana, Ike; Sari, Wiwin Rita; Wardany, Kusuma; Komarudin, Agus; Zulkarnain, Ferdi (Gapenas Publisher, 2025)
This activity was carried out through training for teachers at UPTD SDN 4 Pakuan Aji. The aim was to assist teachers in creating more engaging learning media that align with the Merdeka Curriculum. The implementation method consisted of four stages: warming up, presentation, training, and closing. The subjects were 13 teachers from UPTD SDN 4 Pakuan Aji. This activity was motivated by the need for teachers to gain knowledge about literacy-numeracy-based and digital literacy-numeracy-based learning models, as the Merdeka Belajar program from the Ministry of Education and Culture has not yet been fully absorbed by the teachers.The results showed an increase in enthusiasm and changes in participants' behavior at each stage of the activity, as well as improved understanding of literacy and numeracy-based learning models. This was evident from a brief teaching demonstration conducted by one of the teachers from UPTD SDN 4 Pakuan Aji.